2012
DOI: 10.1159/000336122
|View full text |Cite
|
Sign up to set email alerts
|

Illicit Drug Use in the Flemish Nightlife Scene between 2003 and 2009

Abstract: Aims: Given the importance of party people as innovators and early adaptors in the diffusion of substance use, and given the lack of longitudinal scope in studies of the nightlife scene, we explored changes in illicit drug use among young people participating in the nightlife scene in Flanders. Methods: A survey among party people selected at dance events, rock festivals and clubs was held in the summer of 2003 and repeated in 2005, 2007 and 2009. In total, 2,812 respondents filled in a questionnaire on the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Compared with previous studies conducted in nightlife settings, the present study showed a similarly high prevalence of illicit drug use during the previous year as that among club goers in Norway (43%) [20] and among staff at licensed premises in Stockholm (47% among 18-to 24-year-olds) [56]. Furthermore, in line with previous studies, the most commonly used drugs were cannabis, followed by ecstasy, cocaine, and amphetamine [4,[11][12][13]15,17,20,[23][24][25][26][27]41]. Moreover, 11% of participants reported last-year use of ketamine.…”
Section: Prevalence Of Illicit Drug Use and Settings Where Drugs Are Usedsupporting
confidence: 87%
See 1 more Smart Citation
“…Compared with previous studies conducted in nightlife settings, the present study showed a similarly high prevalence of illicit drug use during the previous year as that among club goers in Norway (43%) [20] and among staff at licensed premises in Stockholm (47% among 18-to 24-year-olds) [56]. Furthermore, in line with previous studies, the most commonly used drugs were cannabis, followed by ecstasy, cocaine, and amphetamine [4,[11][12][13]15,17,20,[23][24][25][26][27]41]. Moreover, 11% of participants reported last-year use of ketamine.…”
Section: Prevalence Of Illicit Drug Use and Settings Where Drugs Are Usedsupporting
confidence: 87%
“…The age of onset was lowest for cannabis (median: 17; interquartile range (IQR): 16-19) and highest for ketamine (median: 23; IQR: 21-27) (Figure 3). The median age of onset was 20 for magic mushrooms (IQR: 19-23) and 21 for ecstasy (IQR: 19-23), amphetamine (IQR: 19-23), cocaine (IQR: 19-24), and LSD (IQR: [19][20][21][22][23][24]. As a comparison, the median age for first use was 15 for alcohol (IQR: 14-16) and 16 for tobacco products (IQR: 14-17), respectively.…”
Section: Age and Gendermentioning
confidence: 99%
“…Subsequent surveys have confirmed continued high levels of mephedrone use in the gay dance clubs under discussion, with mephedrone remaining the most popular drug, with fieldwork night use increasing from 27% of south London gay dance club-goers in 2010 to 43% in 2011 [10,11]. We suggest that on balance research on ‘early adopters, adaptors and innovators' of psychostimulant/club drug trends provides crucial information for anticipating possible trends whilst also addressing the concerns of underestimation of drug use in general population surveys [33]. …”
Section: Limitationsmentioning
confidence: 99%
“…In Australia, previous data collection has relied on self‐reported information from sentinel populations, including ‘recreational’ or ‘party drug’ cohorts (e.g. ), but these data may not be representative of use and related harms across the community.…”
Section: Introductionmentioning
confidence: 99%